Blue Economy and the Attraction of Beach Tourism - AURELIA, Devina; SETYAWATI, Ni Kadek; MORUK, Mariane Clarissa; CAHYANI, Ni Made Melia (PT Batara Swastika Harati, 2024)
The Blue Economy is a sustainable development strategy that integrates economic growth, marine environmental conservation, and social welfare. This concept emphasizes the importance of balancing the utilization of marine resources with long-term ecosystem sustainability. In the context of tourism, the Blue Economy offers opportunities to develop coastal attractions that are both economically valuable and environmentally responsible. This article aims to analyze the relationship between the Blue Economy and the development of coastal tourism attractions. The method applied is a systematic literature review of 15 relevant national and international journals that discuss sustainable marine resource management, coastal tourism, and community involvement. The findings show that the application of Blue Economy principles not only ensures the sustainability of coastal ecosystems but also increases economic added value through sustainable tourism, marine-based product innovation, and local community empowerment. Furthermore, this study emphasizes the importance of multi-stakeholder collaboration including government, private sector, and local communities in designing policies and strategies that encourage sustainable coastal tourism development rooted in the Blue Economy framework.